Evaluation of ketamine and bupivacaine with xylazine for epidural analgesia in buffalo calves - SINGH, V; A, AMARPAL; KINJAVDEKAR, P; AITHAL, H P; PAWDE, A M (The Indian Journal of Animal Sciences, 2010)
The effects of epidural ketamine and bupivacaine with xylazine were evaluated and compared on the basis of analgesic, physiological and haemodynamic parameters in buffaloes. Xylazine (0.05 mg/kg) alone and combinations of xylazine and ketamine (0.05 mg/kg and 2.0 mg/kg), and xylazine and bupivacaine (0.05 mg/kg and 0.125 mg/kg) were administered epidurally in 4 animals each, randomly. Combination of xylazine with ketamine or bupivacaine produced complete analgesia of tail, perineum, inguinal region and upper parts of hind limbs. Xylazine/ketamine produced early onset and more depth of analgesia with less decrease in respiratory rate as compared to xylazine alone or xylazine/bupivacaine combination. Xylazine/bupivacaine produced significantly more depth and longer duration of analgesia than that produced by xylazine, but caused slightly more decrease in mean arterial pressure than xylazine/ketamine. The ECG changes were more obvious in xylazine/bupivacaine group than the animals of xylazine/ketamine group. It was concluded that both ketamine and bupivacaine can enhance the depth of analgesia produced by xylazine. Ketamine can also enhance the onset of analgesia and mitigate some of the side effects of xylazine in buffaloes